The Chloride Conductance Inhibitor NS3623 Enhances the Activity of a Non-selective Cation Channel in Hyperpolarizing Conditions - Monedero Alonso, David; Pérès, Laurent; Hatem, Aline; Bouyer, Guillaume; Egée, Stéphane (Frontiers in Physiology, 2021)
Handbooks of physiology state that the strategy adopted by red blood cells (RBCs) to preserve cell volume is to maintain membrane permeability for cations at its minimum. However, enhanced cation permeability can be measured and observed in specific physiological and pathophysiological situations such as in vivo senescence, storage at low temperature, sickle cell anaemia and many other genetic defects affecting transporters, membrane or cytoskeletal proteins. Among cation pathways, cation channels are able to dissipate rapidly the gradients that are built and maintained by the sodium and calcium pumps. These situations are very well documented but a mechanistic understanding of complex electrophysiological events underlying ion transports is still lacking. In addition, non-selective cation (NSC) channels present in the RBC membrane have proven difficult to molecular identification and functional characterization. For instance, NSC channel activity can be elicited by Low Ionic Strength conditions (LIS): the associated change in membrane potential triggers its opening in a voltage dependent manner. But, whereas this depolarizing media produces a spectacular activation of NSC channel, Gárdos channel-evoked hyperpolarizations have been shown to induce sodium entry through a pathway thought to be conductive and termed Pcat. Using the CCCP method, which allows to follow fast changes in membrane potential, we show here i/ that hyperpolarization elicited by Gárdos channel activation triggers sodium entry through a conductive pathway, ii/ that chloride conductance inhibition unveils such conductive cationic conductance, iii/ that the use of the specific chloride conductance inhibitor NS3623 (a derivative of Neurosearch compound NS1652), at concentrations above what is needed for full anion channel block, potentiates the non-selective cation conductance. These results indicate that a non-selective cation channel is likely activated by the changes in the driving force for cations rather than a voltage dependence mechanism per se.